Analisis Sistematis Strategi Pembelajaran Berdiferensiasi dalam Matematika: Optimalisasi Potensi Unik dan Hasil Belajar Peserta didik - Nidia Winda Sari (PT PUSTAKA CENDEKIA GROUP, 2024)
Education that responds to the individual needs of students is key to optimizing each learner's unique potential. Differentiated instruction emerges as a solution to accommodate the diversity of students' interests, learning styles, and abilities. This study aims to systematically analyze the implementation of differentiated instruction strategies in mathematics and their impact on student learning outcomes. The method used is a Systematic Literature Review (SLR), focusing on journals published in Indonesia. Selected articles center on differentiated instruction in the context of junior and senior high school students, employing experimental or classroom action research (CAR) methods. Out of 175 articles identified, 20 articles were selected following a screening process based on inclusion and exclusion criteria. The analysis shows that differentiated instruction strategies consistently have a positive impact on students' mathematical problem-solving skills, creative thinking, and learning motivation. This study provides valuable insights for educators to design adaptive and innovative teaching strategies to enhance the quality of mathematics education.